The Effect of Medical Service Quality on Patient Satisfaction and Its Impact on Patient Loyalty (Study at The General Clinic of Puri Asih Hospital, Karawang Regency) - Nur Aisyah, Anita; Komar Priatna, Deden; Roswinna, Winna (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
In addition to the problem of Service Quality, low Patient Loyalty is suspected to be due to Patient Satisfaction, because Service Quality and Patient Satisfaction can provide a strong incentive for Personnel to work optimally to achieve high Patient Loyalty. The purpose of this study was to find out and analyze: (1) Service Quality (2) Patient Satisfaction; (3) Patient Loyalty; (4) the influence of Service Quality on Patient Satisfaction; (5) the influence of Service Quality on Patient Loyalty; and (6) the magnitude of the influence of patient satisfaction on patient loyalty in the general clinic of Puri Asih Hospital, Karawang regency. The research method used in this study was a descriptive survey and an explanatory survey. The unit of analysis in this study was staff at the Puri Asih Hospital Public Clinic, Karawang Regency, with a population of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of research and discussion, it was found that the quality of services provided was inadequate, patient satisfaction was considered quite satisfied, patient loyalty was considered quite high, service quality had an effect on patient satisfaction, service quality had an effect on patient loyalty and patient satisfaction had had an effect on patient loyalty. between Service Quality and Patient Loyalty satisfaction which influence Patient Loyalty, it turns out that Service Quality has a dominant influence. Because Service Quality has a dominant influence on Patient Loyalty rather than Patient Satisfaction, it is advisable to create a pleasant work atmosphere, so that they are able to work more professionally.